Dynamic channel allocation scheme for mobile satellite systems - Anthony, Angeline; Habaebi, Mohamed Hadi; Talib, Sahar; Mohd. Ali, Borhanuddin (IEEE, 2003)
A new dynamic channel allocation scheme (DCAS) has been proposed for mobile satellite systems with the aim of improving the utilization of the network resources by reducing the handoff call dropping probability (HODP) while guaranteeing a certain quality of service for the new call blocking probability (NCBP). The arriving calls are given channels based on their priority. The handoff calls have higher priority compared to the new calls, and real time traffic calls have higher priority over non real time calls. The DCAS is then combined with the shortest path routing for a adaptive channel management scheme.